Penguatan Budaya Literasi di Pondok Pesantren El Karim Cibuah Warunggunung Lebak Banten Melalui Gerakan Literasi - Hendrieta Ferieka; Ahmad Habibi Syahid; Falikh Alhaq (Universitas Serang Raya, 2023)
Banten as a province, is also known as an area with the nickname